Desenvolvimento de procedimentos analíticos limpos para a determinação de cloreto e demanda química de oxigênio em águas - Silva, Claudineia Rodrigues da (2004)
The work here described deals with the development of clean analytical methods for determination of chloride and chemical oxygen demand in water samples. A flow injection spectrophotometric method was developed for determining chloride in water samples based on a solid phase reactor (SPR) containing Hg(SCN)2. The solid reagent was immobilized in epoxy resin. The solid phase reactor was regenerated using an intermittent flow of a solution containing 0.12% m v-1 Hg(SCN)2 and this strategy was needed for baseline stabilization. The analyte chloride displaces thiocyanate from the SPR and this latter reacts with Fe(III) forming a red complex measured at 480 nm. The lifetime of the reactor was estimated in 1000 injections, and both the reagent consumption and the waste generation were appreciably reduced. The obtained results were in agreement with a standard method at a 95% confidence level. The relative standard deviation was 2.25% for 10 successive injections of a 8.0 mg L-1 Cl- solution, and the analytical frequency was 100 determinations h-1. Two metallic electrodes, copper and nickel, were built for determination of chemical oxygen demand (COD). The copper electrode was used in voltammetric measurements in the 0.25 to 0.70 V potential range (vs. Ag/AgCl). The analytical curves were obtained using reference solutions containing from 477 to 2800 mg L-1 glucose.The detection limit was estimated in 152 mg L-1 and the relative standard deviation was < 0.5% (n = 4) for a sample containing 2800 mg L-1 glucose. Voltammetric measurements for COD determination using the Ni electrode were made in the potential range of 0.25 to 0.50 V (vs. Ag/AgCl). The analytical curve was obtained using solutions containing from 48 to 469 mg L-1 of COD. The detection limit was estimated in 7.7 mg L-1 and the relative standard deviation was <2.0% (n = 3) for a sample containing 469 mg L-1 glucose. The voltammetric methods employing Cu/CuO e Ni/NiO electrodes were applied for COD determination in residual waters of food industry and the obtained results were compared with those obtained using a standard method. The conventional methods are usually based on toxic reagents and the time of analysis is around 4 h. The residual solution is either stored or its discard is expensive. The main advantage of the proposed voltammetric methods is that no toxic reagent is used and the time of analysis is shorter, i.e. around 30 min.